2009
DOI: 10.1093/intqhc/mzp003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of US accredited and non-accredited rural critical access hospitals

Abstract: The results indicate that in the setting of critical access hospitals, external accreditation appears to result in modestly better performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 19 publications
3
34
0
2
Order By: Relevance
“…A total of 42 studies examined the development and impacts of accreditation programmes 3 6 21 25 26 29–31 51 54 55 57 59–61 64 66 70 71 73 75 80–82 84 86 88 93 96 98 100–109 122 128. A combination of positive, negative and neutral impacts were identified (see table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 42 studies examined the development and impacts of accreditation programmes 3 6 21 25 26 29–31 51 54 55 57 59–61 64 66 70 71 73 75 80–82 84 86 88 93 96 98 100–109 122 128. A combination of positive, negative and neutral impacts were identified (see table 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, notwithstanding the commonly accepted perceptions by governments (El-Jardali et al, 2008) and healthcare professionals (Diab, 2011;El-Jardali et al, 2008) on the benefits of accreditation; existing evidence is either modest Lutfiyya et al, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 r n a l o f H e a l t h O r g a n i z a t i o n a n d M a n a g e m e 3 2009) or inconclusive (Bogh et al, 2015;Braithwaite et al, 2010;Dean Beaulieu and Epstein, 2002;Greenfield and Braithwaite, 2008;Miller et al, 2005;Shaw et al, 2010;Thornlow and Merwin, 2009), particularly regarding its impact on the quality of care. For example, findings from a study of 216 state psychiatric hospitals in the U.S. revealed a weak association between accreditation and the seven indicators of quality of care selected (average cost per patient, per diem bed cost, total staff hours per patient, clinical staff hours per patient, percent of staff hours provided by medical staff bed turnover, and percent of beds occupied) (Hadley and McGurrin, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of rural critical access hospitals in the USA (19) found that accredited hospitals showed significant advantage over non-accredited hospitals in 4 out of 16 clinical indicators but noted that, in a sector where only one third of hospitals seek accreditation, self-selection and motivation could explain much of this advantage.…”
Section: Controlled Studiesmentioning
confidence: 99%